Cellular senescence and senescence‐associated secretory phenotype via the cGAS‐STING signaling pathway in cancer - Loo, Tze Mun; Miyata, Kenichi; Tanaka, Yoko; Takahashi, Akiko (Cancer science, 2020)
Cellular senescence is historically regarded as a tumor suppression mechanism to prevent damaged cells from aberrant proliferation in benign and premalignant tumors. However, recent findings have suggested that senescent cells contribute to tumorigenesis and age‐associated pathologies through the senescence‐associated secretory phenotype (SASP). Therefore, to control age‐associated cancer, it is important to understand the molecular mechanisms of the SASP in the cancer microenvironment. New findings have suggested that the cyclic GMP‐AMP synthase (cGAS)‐stimulator of interferon genes (STING) signaling pathway, a critical indicator of innate immune response, triggers the SASP in response to accumulation of cytoplasmic DNA (cytoplasmic chromatin fragments, mtDNA and cDNA) in senescent cells. Notably, the cGAS‐STING signaling pathway promotes or inhibits tumorigenesis depending on the biological context in vivo, indicating that it may be a potential therapeutic target for cancer. Herein, we review the regulatory machinery and biological function of the SASP via the cGAS‐STING signaling pathway in cancer. This brief review discusses the role of the senescence‐associated secretory phenotype (SASP) and cyclic GMP‐AMP synthase‐stimulator of interferon genes (cGAS‐STING) signaling pathway on cellular senescence in cancer development. We suggest that the cGAS‐STING signaling pathway may be a novel target for induction of SASP.